(3JcfhdhLjG GdeYdheGJ h RjGOI GdUGOQGJ h OYe GdJfejI GdUfGYjI (B/s - (3YHO GdQRGb, eMehO MGeO eMehOs ((3GdbGgQI(B: s (3ecJHI GdMQjI ddfTQ hGdJhRjY(B, s, 2006)
(3jVe JLGQH HYV GdOhd GdESdGejI aj JcfhdhLjG GdeYdheGJ hGdJLGQI GdEdcJQhfjI, GdCgejI GdEbJUGOjI dJcfhdhLjG GdeYdheGJ hGdJLGQI GdEdcJQhfjI, OhQ JcfhdhLjG GdeYdheGJ aj JMSjf COGA GdUGOQGJ GdUfGYjI GdeUQjI, edNU hfJGFL hJhUjGJ GdOQGSIs
(3HjHdjhZQGajG(B: (3U U(B.273-304s
Keywords: (3GdJcfhdhLjG(B- (3NOeGJ GdeYdheGJs; (3GdJfejI GdGbJUGOjIs; (3GdJfejI GdUfGYjIs